Long term biventricular resynchronisation therapy in advanced heart failure: effect on neurohormones. Issue 5 (14th April 2005) - Braun, M U; Rauwolf, T; Zerm, T; Schulze, M; Schnabel, A; Strasser, R H
Abstract : Objective: To assess prospectively the effect of cardiac resynchronisation therapy (CRT) on New York Heart Association (NYHA) functional class, cardiac function, cardiopulmonary exercise performance, and neurohormonal activation during 24 months' follow up. Design: Controlled study. Patients and Results: 124 patients with severe congestive heart failure (ejection fraction < 35%, NYHA III–IV) and left bundle branch block (QRS duration > 150 ms) were enrolled (control group, n  =  59; CRT group, n  =  65) and followed up at 1, 3, 12, and 24 months. Compared with the control group, CRT led to significant short and long term improvements in functional NYHA functional class (mean (SEM) 2.1 (0.4) v 2.8 (0.4) at 24 months, p < 0.05), mean ejection fraction (25.7 (4)% v 21.1 (5)% at 24 months, p < 0.05), peak Vo 2 (16.8 (3.9) v 12.6 (3.5) ml/kg × min at 24 months, p < 0.01), and Vo 2 at anaerobic threshold (14.4 (3.7) v 10.8 (3.2) ml/kg × min at 24 months, p < 0.05). In addition, CRT for one and 12 months significantly decreased the plasma concentrations of noradrenaline (norepinephrine) and N-terminal fragment of pro-brain natriuretic peptide, whereas no changes were observed for other neurohormones such as antidiuretic hormone, aldosterone, and endothelin. Conclusion: Long term CRT (⩽ 24 months) results in significant improvement of NYHA class and cardiopulmonary exercise capacity and a short term decrease in neurohormonal activation.